Barbados, Bathsheba. - (:unkn) unknown (The Main Library, University of the West Indies, Cave Hill Campus, Barbados is responsible for making this digital resource available., 2024)
Postcard showing the hills and fields of Bathsheba, Barbados. In the foreground there are two persons. Houses and coconut trees are in the background. The railroad tracks are seen between the seacoast and the houses. This is a divided back postcard. On the back of the postcard AL HNT £3. Feb – 13-1912. Feeling fine. Julius. Mr. Joseph McCurry, 7310 Susquehanna St., Pittsburgh, Pa. U.S.A. No. 16 Copyright Knight & Co.
Landscape; Black & white; 3 ½” x 5 ½”
Keywords: Hills; Houses; Trees; Railroads; Railroad tracks; Coastlines; Bathsheba, Barbados.